Penile Trauma in a Pediatric Patient Caused by Physical Abuse: A Case Report - Dahril; Garbie Syahly Agung (Jurnal Health Sains, 2026)
Penile trauma in pediatric patients is a rare but clinically significant condition. While most cases result from accidental mechanisms such as falls or sports injuries, clinicians must maintain a high index of suspicion for non-accidental injury (NAI), particularly when the presenting history is inconsistent with the injury pattern or when the mechanism involves interpersonal violence. This case report aims to describe the clinical presentation, diagnostic evaluation, surgical management, and outcome of an 8-year-old boy who sustained penile trauma following suspected physical abuse. A descriptive observational design in the form of a case report was employed. Data were collected retrospectively from the patient's medical records, encompassing demographic information, clinical history, physical examination findings, imaging studies (ultrasonography with Doppler), treatment interventions, and postoperative outcomes. The patient presented with progressive penile swelling and pain. Imaging revealed intact corpora cavernosa and corpus spongiosum, with soft tissue oedema and fluid collection at the distal glans. Initial conservative management was insufficient, necessitating surgical intervention comprising debridement, penile reconstruction, and defect closure using a complex local flap technique combined with circumcision. Postoperatively, the patient demonstrated gradual wound healing with no signs of surgical site infection or early postoperative complications. The possibility of non-accidental injury should always be considered in pediatric penile trauma, particularly in cases with an inconsistent history or delayed presentation. Ultrasonography with Doppler is a valuable non-invasive imaging modality for the assessment of penile injuries. When conservative management is inadequate or presentation is delayed, timely surgical reconstruction using local flap techniques can achieve favorable functional and cosmetic outcomes while minimizing long-term morbidity.